Quality of Health Services at Ilu Health Center of Ilu District, Puncak Jaya Regency, Central Papua Province - Siron Kogoya,; Abdul Rahman Dilapanga,; Itje Pangkey, (Technium Social Sciences Journal, 2025)
The purpose of this study was to determine and analyze the quality of outpatient services at the Ilu Health Center, Ilu District, Puncak Jaya Regency. This study uses a qualitative method with research indicators, namely the mechanism of health center services, medical personnel, health center facilities, and community response. The result of the study showed that the service quality of Ilu Health Center demonstrates both strengths and areas for improvement. Emergency patients receive prompt attention, but delays for non-emergency cases due to staff absenteeism impact satisfaction. While procedures are simple and accurate, insufficient equipment and inconsistent staff discipline reduce service effectiveness. Although services are free and align with Decree of the Minister of State Apparatus Empowerment No. 63/KEP/M.PAN/7/2003, facility limitations, such as inadequate parking and medical records management, hinder efficiency. Medical personnel exhibit professionalism through clear communication and competence, fostering patient trust. Cleanliness and proper staff uniforms reflect high standards, though the lack of sufficient parking and a garden detracts from the experience. Mechanisms like suggestion boxes and equitable treatment of all patients align with participatory and ethical service principles. Staff accountability in handling challenges, such as equipment shortages, enhances trust further. To optimize service quality, the Ilu Health Center needs improvements in staff discipline, infrastructure, and resource management. Addressing these areas will strengthen alignment with public service principles and health standards, ultimately enhancing patient satisfaction and trust.